Research progress on the risk factors of peripherally inserted central catheter-related bloodstream infection in elderly patients with malignant tumors (老年恶性肿瘤患者并发经外周置入中心静脉导管相关血流感染危险因素研究进展) - YU Fujuan (于福娟); CUI Lingling (崔玲玲) (Association of Integrative Nursing, 2024)
Peripherally inserted central catheter (PICC) represent one of the most common modes of central venous access used in chemotherapy and enteral nutrition in elderly patients with malignant tumors. However, the clinical application of PICC may cause a series of complications including infection, catheter blockage, thrombosis, catheter dislocation, etc. The catheter-related bloodstream infection (CRBSI) is one of the most serious complications after PICC placement. This paper reviewed studies on risk factors of PICC-related infection in elderly patients with malignant tumors, in order to provide reference for clinical practice. (经外周置入中心静脉导管(PICC)是老年恶性肿瘤患者化疗、肠外营养支持等治疗的首选静脉通路。PICC置管可能引发感染、导管堵塞、血栓形成、导管异位等并发症, 其中导管相关血流感染(CRBSI)是最严重的并发症之一。本研究就老年恶性肿瘤PICC置管患者并发CRBSI的相关危险因素的研究进展进行综述, 旨在为临床针对性的防治提供参考。)